Accompaniment Learning Media Development to Increase The Elementary School Teacher Competence - Wahyudi, Wahyudi; Chamdani, Muhammad; Suryandari, Kartika Chrysti; Rokhmaniyah, Rokhmaniyah (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2019)
One of the problems faced by elementary school teachers is the problem of making and using learning media in schools.This is due to the lack of readiness of human resources about understanding media in learning. For this purpose the community service activities are: (1) increasing the competence of elementary school teachers about learning, (2) developing learning media in elementary schools, (3) structuring learning media in elementary schools. This Community Service activity uses the design of the transfer of science and technology from the university to the stakeholders which includes: (a) workshops, (b) training and mentoring. This dedication activity was carried out in the activities of the  Teachers Working Group Cluster "Banyumudal" in Kebumen District year  2019. The results of these community service activities are: (1) improvement of teacher competency about learning media in elementary schools, (2) products of various types of learning media in elementary schools, (3) the formation of "Mini Laboratory" for learning in elementary schools